Albrecht dürer's Material World. - Wouk, Edward H. (Book collections on Project MUSE., 2023)
This highly illustrated catalogue presents new essays on Albrecht Dürer, focusing on an understudied aspect of his practice: the material worlds of manufacture, design and trade.